Diseño de un módulo para la validación del algoritmo de denavit-hartenberg de un brazo antropomórfico aplicado al área de automatización. (2021)
This project was carried out in order to design a robotic arm for didactic purposes, whose main function is to support the teaching methodologies taught by the teachers in the laboratories. Implementing the use of a tool widely implemented in industries today, means a positive and enriching approach for students, because simulating a work environment with devices that today take much more power, turns out to be a great complement with the knowledge imparted by teachers.